Minor Universality / Universalité mineure (De Gruyter, 2023)
In times of relativism – marked by the critique of Western universalism on the one hand, and resurgent identitarian and neo-nationalistic claims to identity on the other, this volume tracks the development and relevance of cultural and social practices that posit forms of minor universality, asking: Where and how do contemporary practices open up concrete settings so as to create experiences, reflections and agencies of a shared humanity?